Drosophila melanogaster as a model for unraveling unique molecular features of epilepsy elicited by human GABA transporter 1 variants - Ameya S. Kasture; Ameya S. Kasture; Florian P. Fischer; Florian P. Fischer; Lisa Kunert; Melanie L. Burger; Alexander C. Burgstaller; Ali El-Kasaby; Thomas Hummel; Sonja Sucic (Frontiers in Neuroscience, 2023)
Mutations in the human γ-aminobutyric acid (GABA) transporter 1 (hGAT-1) can instigate myoclonic-atonic and other generalized epilepsies in the afflicted individuals. We systematically examined fifteen hGAT-1 disease variants, all of which dramatically reduced or completely abolished GABA uptake activity. Many of these loss-of-function variants were absent from their regular site of action at the cell surface, due to protein misfolding and/or impaired trafficking machinery (as verified by confocal microscopy and de-glycosylation experiments). A modest fraction of the mutants displayed correct targeting to the plasma membrane, but nonetheless rendered the mutated proteins devoid of GABA transport, possibly due to structural alterations in the GABA binding site/translocation pathway. We here focused on a folding-deficient A288V variant. In flies, A288V reiterated its impeded expression pattern, closely mimicking the ER-retention demonstrated in transfected HEK293 cells. Functionally, A288V presented a temperature-sensitive seizure phenotype in fruit flies. We employed diverse small molecules to restore the expression and activity of folding-deficient hGAT-1 epilepsy variants, in vitro (in HEK293 cells) and in vivo (in flies). We identified three compounds (chemical and pharmacological chaperones) conferring moderate rescue capacity for several variants. Our data grant crucial new insights into: (i) the molecular basis of epilepsy in patients harboring hGAT-1 mutations, and (ii) a proof-of-principle that protein folding deficits in disease-associated hGAT-1 variants can be corrected using the pharmacochaperoning approach. Such innovative pharmaco-therapeutic prospects inspire the rational design of novel drugs for alleviating the clinical symptoms triggered by the numerous emerging pathogenic mutations in hGAT-1.